Membangun generasi melalui pendidikan: Peran YPMAK dalam Pemberdayaan Masyarakat Amungme & Kamoro - Atek, Liboria Genoveva (CENDERAWASIH: Jurnal Antropologi Papua, 2024)
Education is a determinant of the success of a nation as evidenced by the increase in the Human Development Index. Yayasan pemberdayan masyarakat Amungme dan Kamoro (YPMAK) is a supporter in the community empowerment program of the Amungme and Kamoro tribes and five other tribes. The method used in this research is descriptive qualitative, the type of approach using literature study (liberary research). The result of this research is the non-profit Yayasan pemberdayan masyarakat Amungme dan Kamoro (YPMAK), as the manager of the 1% fund from PT Freeport Indonesia. Education program in 2022: 45 scholarship recipients have completed their undergraduate education. Sekolah Asrama Taruna Papua (SATP) became the school with the most interested 245 children. Lack of educators, lack of educational facilities and infrastructure and the distance between the district capital and the school is very far. It is recommended that YPMAK increase the number of educators, improve educational facilities, and provide more adequate transportation access for students from remote areas.